Mechanical Power Correlates With Lung Inflammation Assessed by Positron-Emission Tomography in Experimental Acute Lung Injury in Pigs - Scharffenberg, Martin; Wittenstein, Jakob; Ran, Xi; Zhang, Yingying; Braune, Anja; Theilen, Raphael; Maiello, Lorenzo; Benzi, Giulia; Bluth, Thomas; Kiss, Thomas; Pelosi, Paolo; Rocco, Patricia R. M.; et al. (Frontiers in Physiology, 2021)
Background: Mechanical ventilation may initiate or worsen lung injury, so-called ventilator-induced lung injury (VILI). While different mechanisms of VILI have been identified, research mainly focused on single ventilator parameters. The mechanical power (MP) summarizes the potentially damaging effects of different parameters in one single variable, and has been shown to be associated with lung damage. However, to date the association of MP with pulmonary neutrophilic inflammation, as assessed by positron-emission tomography (PET), has not been prospectively investigated in a model of clinically relevant ventilation settings yet. We hypothesized that the degree of neutrophilic inflammation correlates with MP. Methods: Eight female juvenile pigs were anesthetized and mechanically ventilated. Lung injury was induced by repetitive lung lavages followed by initial PET and computed tomography (CT) scans. Animals were then ventilated according to the ARDS network recommendations, using the lowest combinations of positive end-expiratory pressure and inspiratory oxygen fraction that allowed adequate oxygenation. Ventilator settings were checked and adjusted hourly. Physiological measurements were conducted every 6 h. Lung imaging was repeated 24 h after first PET/CT before animals were killed. Pulmonary neutrophilic inflammation was assessed by normalized uptake rate of 2-deoxy-2-[18F]fluoro-D-glucose (KiS) and its difference between the two PET/CT was calculated (∆KiS). Lung aeration was assessed by lung CT scan. MP was calculated from the recorded pressure-volume-curve. Statistics included Wilcoxon tests and non-parametric spearman correlation. Results: KiS increased significantly from first to second PET/CT (P=0.012). ∆KiS significantly correlated with median MP (ρ=0.738, P=0.037) as well as its elastic and resistive components, but neither with median peak, plateau, end-expiratory, driving and transpulmonary driving pressures, nor respiratory rate, elastance or resistance. Lung mass and volume significantly decreased while relative mass of hyper-aerated lung compartment increased after 24 h (P=0.012, P=0.036, and P=0.025, respectively). Resistance and PaCO2 were significantly higher (P=0.012 and P=0.017, respectively), while respiratory rate, end-expiratory pressure, and MP were lower at 18 h compared to start of intervention. Conclusions: In this model of experimental acute lung injury in pigs, pulmonary neutrophilic inflammation evaluated by PET/CT increased after 24 hours of mechanical ventilation, and correlated with MP.